Hydrophobicity of Thin Films of Compounds of Low‐Electronegativity Metals. Issue 9 (4th August 2014) - Zenkin, Sergei; Kos, Šimon; Musil, Jindřich; Rohrer, G.
<x xml:space="preserve">Abstract</x> Hydrophobic materials capable of withstanding harsh conditions are required for various applications. Here, we show that oxides and nitrides of various low‐electronegativity metals are hydrophobic hard ceramics. We attribute their hydrophobicity to low Lewis acidity of the low‐electronegativity cations implying a low ability of the cations on the surface to form coordinate bonds with water oxygen anions. Furthermore, we observe a systematically stronger hydrophobic behavior of nitrides compared with the corresponding oxides, which we attribute to nitrogen being a poorer Lewis base than oxygen due to a reduced number of lone pairs of electrons, implying a lower ability of nitrogen anions on the surface to form hydrogen bonds with water hydrogen cations. Most of the oxides and nitrides investigated exhibit high values of hardness. Therefore, oxides and nitrides of low‐electronegativity metals should find application as hydrophobic materials in harsh conditions.